2018
DOI: 10.1021/acs.iecr.8b00181
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Study of Solid-Phase Formation during the Decompression of High-Pressure CO2 Pipelines

Abstract: Decompression of CO2 pipelines is studied both experimentally and numerically to provide a validated model as the basis for the prediction of the hazards associated with CO2 solid formation. The pipeline decompression experiments, performed using a fully instrumented 36.7 m long and 50 mm internal diameter test pipe up to a maximum pressure of 45 bar, incorporating discharge orifice diameters of 4 and 6 mm, reveal the stabilisation of pressure and temperature near the CO2 triple point. Also, video recordings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As such, the model indicates that decompression of a compressed CO2 gas state doesn't lead to CO2 solids forming in the pipe. Figure 3 shows the effect of d/D ratio on the mass of solid CO2 formed in the pipe upon its decompression to the triple point, obtained based on the HEM flow model predictions, in comparison with estimates using the thermodynamic method assuming isentropic decompression [12]. As can be seen in Figure 3, predictions by the thermodynamic method are insensitive to the orifice diameter.…”
Section: The Effect Of Initial Conditionsmentioning
confidence: 97%
See 2 more Smart Citations
“…As such, the model indicates that decompression of a compressed CO2 gas state doesn't lead to CO2 solids forming in the pipe. Figure 3 shows the effect of d/D ratio on the mass of solid CO2 formed in the pipe upon its decompression to the triple point, obtained based on the HEM flow model predictions, in comparison with estimates using the thermodynamic method assuming isentropic decompression [12]. As can be seen in Figure 3, predictions by the thermodynamic method are insensitive to the orifice diameter.…”
Section: The Effect Of Initial Conditionsmentioning
confidence: 97%
“…Also, accumulation of solid CO2 in pipelines and vessels may increase the risk of blockage and overfilling of units at later stages of operation [7][8][9][10][11]. In particular, our recent studies showed that solid CO2 may form during decompression of pipelines initially filled with CO2 at 60-80 bar pressures [12,13]. Given that solid CO2 accumulation in safety valves and vented sections of pipelines presents a risk for the system integrity, designing venting equipment and procedures that minimize the amounts of solid phase formed becomes critically important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 This results in the generation of dry ice in the release valve, which blocks the decompression. According to the results of Martynov et al, and Zheng et al's study on the decompression process of CO 2 across the triple-phase point, 38,39 if dry ice is generated in the pipe during the decompression process, a pressure plateau will appear in the pressure drop curve when the triple-phase point pressure is reached. This is consistent with the experimental results, therefore dry ice is also generated in the pipe.…”
Section: Pressure Evolutionmentioning
confidence: 99%
“…Several experimental discharge configurations with large storage conditions [10][11][12][13] have allowed a better understanding and evaluation of the dispersion of a CO 2 cloud. The blowdown of a highly instrumented pipeline has also been deeply studied considering the potential presence of impurities mixed in the CO 2 and their influence on the thermodynamic properties and formation of solids [14], which could lead to clogging and would be a cause of leakage. Ineris has a good knowledge of the source term calculation and dedicated tools which allowed us to focus on dispersion.…”
mentioning
confidence: 99%